'We're going all out for shale:' explaining shale gas energy policy failure in the United Kingdom. (September 2022) - Bradshaw, Michael; Devine-Wright, Patrick; Evensen, Darrick; King, Owen; Martin, Abigail; Ryder, Stacia; Short, Damien; Sovacool, Benjamin K.; Stretesky, Paul; Szolucha, Anna; Williams, Laurence
Abstract: In January 2014, then British Prime Minister David Cameron declared that his government was 'Going all out for Shale.' In November 2019, during an election campaign, Prime Minister Boris Johnson's Conservative Government imposed a moratorium on hydraulic fracturing bringing to a halt industry hopes of developing shale gas in the UK. This paper explores what happened, integrating research employing a mixed methods research design including a review of the literature, expert interviews, household interviews, a series of nationally representative and local surveys, and a content analysis of political testimony. It starts with a brief history of the shale gas debate in the UK and social science research on the issue. It then examines the UK's Shale Gas landscape, and in particular energy policy failure, by considering three issues: first, the framing of the shale gas debate in the national Parliament, exploring the arguments for and against it; second, changing public perceptions and attitudes towards shale gas development; and third, the attitudes and lived experiences of the communities most affected by shale gas exploration activities. These three dimensions are combined to explain the UK Government's shale gas failure to-date. The paper concludes by identifying the lessons learnt from the Government's initial policy failure, both in relation to further shale gas exploration, but also for other technologies required for a future Net-Zero energy system. Highlights: Explains why the UK Government failed to deliver a shale gas exploration programme prior to 2019. Reports on social science research on the shale gas debate in the UK. Presents quantitative and qualitative research at the national and local scale. Considers the wider policy lessons for Net-Zero energy policy in the UK.